IMPLEMENTASI METODE PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN DAN REATIVITAS DALAM MENULIS TEKS PROSEDUR PADA SISWA KELAS VII B SMP SAPTA ANDIKA - Ni Made Dwi Sintia Wulandari; I Nyoman Adi Susrawan; Ida Ayu Made Wedasuwari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2023)
This research is a classroom action research (PTK) which aims to 1) improve skills and creativity in writing procedure texts for class VII B students of SMP Sapta Andika; 2) Knowing the learning steps for implementing the Project Based Learning method in an effort to improve skills and creativity in writing procedural texts for class VII B students of SMP Sapta Andika; 3) Knowing student responses after implementing the Project Based Learning method in learning to write procedural texts. Collecting data in this study using the method of observation, tests and questionnaires. The data that has been obtained is then analyzed using qualitative and quantitative data analysis methods. The results of the research show an increase in the ability and creativity of students in writing procedural texts using the Project Based Learning method which can be seen from the acquisition of the average student score which increases each cycle, namely the acquisition of the average student pretest score which only reaches 69.39 increased in cycle I after the implementation of the Project Based Learning method using video media obtained an average value of 74.87 then in cycle II it increased again after the implementation of the Project Based Learning method using media produced by students' skills with an average class value of 83.29. As for the learning steps from implementing the Project Based Learning method which is able to improve students' ability and creativity in writing procedural texts, namely 1) Determining basic questions, 2) Designing project plans, 3) Arranging implementation schedules, 4) Monitoring students and project progress, 5) Test results, 6) Evaluate experience. The implementation of the Project Based Learning method in learning to write procedural texts received positive responses from students, as indicated by the percentage of strongly agreeing and agreeing on the statements in the questionnaire reaching 94.62%.